The Russia-Ukraine war in Western mediа: A psycholinguistic modelling of the ‘hybrid’ phase - Danyliuk, Ivan; Bohucharova, Olena (East European Journal of Psycholinguistics, 2023)
The article presents a conceptualisation of English-language media discourse in the retrospective of the 'hybrid' phase of the Russia-Ukraine war from 2014 to 2021. The study aims to analyse the psycholinguistic features of the cognitive modelling of the war in Ukraine in English-language media and investigate the psychosemantic components of the Western media audience's attitude towards the war. Psycholinguistic media monitoring, discourse analysis, semantic-cognitive analysis, content analysis, and Semantic Differential (SD) were used to study the media discourse of the Russia-Ukraine war. The results indicate that the discourse is emotionally positive but controversial, which may hinder the Western audience's understanding of the realities of the war. The newspaper media discourse includes psychosemantic components such as neutral concepts like 'conflict' and 'crisis'. These concepts are often expressed through conceptual metaphors such as 'war', which can be viewed as a path, a game, a business, or a theatre. Additionally, euphemisms and abbreviations (such as ATO) are commonly used, along with an abundance of vocabulary that has positive connotations. There has been a shift in emphasis from the strong concept of 'war' to neutral academic nominalisations, such as 'event'. The study's results confirmed the Western media audience's paradoxical perception of the war. As military activity intensifies, positive assessments of the victorious war tend to decrease, leading to a drop in media ratings. These findings have potential applications in studying Western attitudes towards war and in the cognitive modelling of media content. This is particularly relevant given the future dangers of Russian aggression in 2022.Disclosure StatementNo potential conflict of interest was reported by the authors.* Corresponding author: Olena Bohucharova, 0000-0001-5617-9175 bogucharova_o@i.ua